Framing dalam Advokasi Media Isu Transparansi Anggaran oleh Organisasi Masyarakat Sipil Framing in Media Advocacy of Budget Transparency by Civil Society Organization - Agung Hawari Hadi; Sarwititi Sarwoprasodjo; Ivanovich Agusta (Jurnal Komunikasi Pembangunan, 2015)
ABSTRACT  Civil society organizations deliver frames in a press release as a way of communication that voicing  ideology through media advocacy to approach policy makers or the public as well as to stimulate debate and construct a meaning. FITRA selected as research subject by considering their activeness in the media. This research puspose is to comprehend how FITRA consider Indonesia budget transparency issues and their Frame development process through press releases. The press releases colected from 2010 until 2014, analyzed using Bendford and Snow Framing concept: collective action frame. Result shows FITRA frames their press releases by raising unaccountable state budget planning, the welfare of lame, bad examples of leadership, budget politicization, poor government performance and  lack of budget transparency and public participation.  FITRA blames leadership, executive, legislative and political functions. Identification shows people and the country as victims. Solutions carried by FITRA are improved regulation, affirmative action and incentives, budget rationalization and relocation, improving state revenues and reduce the country's debt, budgets monitoring and evaluation, transparency and public participation, PNS rationalization and improvement of the standard used for the state budget. FITRA’s Framing react to the government's solution. FITRA also urge people to be critical to the budget policy and invites the public to participate in the budgeting process, especially the supervision of budgeting and realization.  Keywords: collective action frame, media advocacy, pers release, social movement